The dynamic nature of motivation in language learning: A classroom perspective - Pawlak, Mirosław (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2012)
When we examine the empirical investigations of motivation in second and foreign language learning, even those drawing upon the latest theoretical paradigms, such as the L2 motivational self system (Dörnyei, 2009), it becomes clear that many of them still fail to take account of its dynamic character and temporal variation. This may be surprising in view of the fact that the need to adopt such a process- oriented approach has been emphasized by a number of theorists and researchers (e.g., Dörnyei, 2000, 2001, 2009; Ushioda, 1996; Williams & Burden, 1997), and it lies at the heart of the model of second language motivation proposed by Dörnyei and Ottó (1998). It is also unfortunate that few research projects have addressed the question of how motivation changes during a language lesson as well as a series of lessons, and what factors might be responsible for fluctuations of this kind. The present paper is aimed to rectify this problem by reporting the findings of a classroom-based study which investigated the changes in the motivation of 28 senior high school students, both in terms of their goals and intentions, and their interest and engagement in classroom activities and tasks over the period of four weeks. The analysis of the data collected by means of questionnaires, observations and interviews showed that although the reasons for learning remain relatively stable, the intensity of motivation is indeed subject to variation on a minute-to-minute basis and this fact has to be recognized even in large-scale, cross-sectional research in this area.
Keywords: L2 motivational self system; Motivational changes; Process-oriented view of motivation; Interest and engagement